Rapid Toluidine Blue – A Technique Standardization In Oral Exfoliation Cytology - Dr. A.Mary Antony Praba, Dr. C. Venkataramaniah, Tb. Paarthieban, M. Mohan Dev (Drugs and Cell Therapies in Hematology, 2021)
Oral cancer is one of the most common form of cancer in world and the incidence of occurrence and death rate is very high in countries like India. One of the main cause for oral cancer in tobacco in any form. The level of risk increases when tobacco is used with betel nuts and alcohol. Usually leukoplakia and erythroplakia will act as markers in analyzing the premalignant condition of oral tumors. Usually patients with lesions will be given a oral rinse of 1% toluidine blue followed by a rinse with acetic acid in order to get clarity. A biopsy will be taken in patients with positive toluidine blue stain and the cells will be analyzed after stained with rapid Papanicolaou (PAP) or H&E. This conventional staining method has its own disadvantage and up to our search in journal toluidine blue alone was not done in analyzing early dysplasia detection. Though rapid PAP staining is the most authoritative staining for early detection of oral dysplasia, it has its own disadvantages too with multiple steps. With this study we tried a few modifications in normal toluidine blue staining, standardized the procedure to work specific and rapid with only 3 steps and compared the cytology of rapid toluidine blue (TBr)stained cells alone with both normal toluidine blue (TB) and rapid papanicolaou((PAPr) stained cells. The results were more or less same with one or two negatives on both sides.